Strategi Pengembangan Obyek Wisata Pangandaran - Wulan, Ira Ratna; ., Turtiantoro; Widayati, Wiwik (Journal of Politic and Government Studies, 2013)
Abstract:The research result shows a lack of local Government's role, also a lack of funds from central Government in developing Pangandaran tourism and there is no cooperation in a big scale from private side in the tourist area. The SWOT analysis was offered a development strategy that should be carried out by the local government of Ciamis regency. In connection with this, the local Government streamlines cooperation with local community and formed aware of tourism group in managing Pangandaran tourism as a nature tourist that cannot be found in other areas. For future research is focused on the evaluation of an existing with the previous strategy, so this can be completed, that is from the side of the Government as well as the side of the public. The local government has not been paying attention to environment issues, especially in terms of physical infrastructure to endeavor local Government as a facilitator which means it can accelerate development through the environmental tourist site improvement. This role can be realized through improvements of the planning procedure and assignment rules. Therefore the things that required is the availability of a distinct purpose so that local Government can be focus on exploit the natural resources that already existing in Pangandaranâ€™s area. Beside as a facilitator the local Government also has to be a stimulator which means they can create development strategy through the special measures that can affect the private investor to join partners that is byÂ the local Government corporate with private investor to promote special theme or other events in the area of â€œPangandaranâ€. Keywords: strategy, tourism object, Pangandaran.